Determinants of Health Seeking Behavior among Caregivers of Children Under Five Years Diagnosed with Pneumonia in Endebess Sub County, Kenya - Opuba, Everlyne N. (JOOUST, 2021)
Pneumonia continues to be the second leading cause of both morbidity and mortality in children under five years in Kenya. In part the high burden of the disease arises from delay and inappropriate health seeking by caregivers. Existing literature indicates that the high mortality and morbidity is attributed to poor health seeking behavior for new-born and child health services in 20 high-burden counties in Kenya, Trans-Nzoia County being included. Endebess Sub County contributes to these statistics because caregiver’s reports of delays of 1-14 days before visiting a health facility as evidenced by history of the presenting illness. The overall objective of this study was to identify determinants of health seeking behavior among caregivers of children under 5 years diagnosed with pneumonia in Endebess Subcounty. The specific research objectives were to determine home based care practices, health facility related practice and logistical factors that influence health seeking behavior among caregivers of children under 5 years diagnosed with pneumonia at Endebess Sub-county. A cross-sectional study design was used in this study. Simple random sampling method was used to select caregivers of children under 5 years with pneumonia visiting the 7 public health facilities in Endebess Sub-county for care at the out-patient department and pediatric unit. All the 24 health care workers were interviewed as key informants. Study population consisted of 273 caregivers. Quantitative and qualitative data was collected by use of questionnaire and key informant interview guides. The social demographic determinants of health seeking were: occupation (p=0.001), house-hold income (p=0.001) and level of education (p=0.004). The home-based care practices that were of significance were: knowledge of pneumonia symptoms (p<0.001), available home remedies (p=0.035) and prior lived experience of pneumonia (p<0.001, OR=2). The significant health facility related practices were: availability of drugs (p<0.001), administration of a starting dose (p<0.001), type of drug prescribed (p<0.001), place caregiver seeks treatment (p=0.005), willingness to recommend the facility (p<0.001) and facility of choice (p=0.001). Communication of health information influenced health seeking as follows: adequate instructions (p<0.001), confidence of caregiver to give the right dosage at home (p<0.001), satisfaction level (p<0.001) and shared decision making on choices of antibiotic therapy (p=0.005). Logistical factors identified were distance to the health facility (p=0.029) and economic empowerment (p=0.013). In conclusion, the Kenyan government needs to ensure that 100% transition from primary to secondary school education is realised in the country, diversify income generating activities for its citizens to increase levels of income, improve road network for accessibility, conform to WHO recommendations of minimum walking distance of 5.0 km to a health facility, increase budgetary allocation to the health sector for drugs and other commodities, employ more staff and continuous training of health staff to provide quality health care. To improve health seeking behavior among caregivers, there is need for health facility focal persons to incorporate health education and behavior change communication interventions on pneumonia management at the community and hospital visits as caregivers seek antenatal and postnatal care services